2012
DOI: 10.1073/pnas.1220425110
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase 8 as a functional regulator of nonsmall cell lung cancer

Abstract: The up-regulation of fucosyltransferase 8 (FUT8), the only enzyme catalyzing α1,6-fucosylation in mammals, has been observed in several malignant cancers including liver, ovarian, thyroid, and colorectal cancers. However, the pathological role and the regulatory mechanism of FUT8 in cancers remain largely unknown. In the current study, we report that the expression of FUT8 is up-regulated in nonsmall cell lung cancer (NSCLC) and correlates with tumor metastasis, disease recurrence, and poor survival in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
201
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(213 citation statements)
references
References 33 publications
9
201
3
Order By: Relevance
“…Consistent with our present observation, they also reported that expression of FUT8 correlated with poor survival in patients with NSCLCs. However, their analyses included cases with noncurative and curative resection, and 45 of 140 cases (32%) were classified as stage IV with metastasis [28]. In the present study, we have clarified for the first time that expression of FUT8 correlates with a short survival period and poor prognosis in patients with curatively resected and pStage I NSCLCs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with our present observation, they also reported that expression of FUT8 correlated with poor survival in patients with NSCLCs. However, their analyses included cases with noncurative and curative resection, and 45 of 140 cases (32%) were classified as stage IV with metastasis [28]. In the present study, we have clarified for the first time that expression of FUT8 correlates with a short survival period and poor prognosis in patients with curatively resected and pStage I NSCLCs.…”
Section: Discussionmentioning
confidence: 68%
“…Loss of core fucose on epidermal growth factor receptor and transforming growth factor β 1 receptor reduces the ligand binding ability as well as downstream signaling [26,27]. Recently, Chen et al [28] have reported that expression of FUT8 is involved in the malignant behaviors of lung cancer cell lines, including in vitro invasion and cell proliferation, as well as in vivo metastasis and tumor growth. Using glycoproteomic and microarray analyses, they have shown that FUT8 globally modifies cell surface antigens, receptors, and adhesion molecules and that it is involved in the regulation of many genes associated with malignancy, suggesting that FUT8 contributes to tumor progression through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the N-glycosylation process can be related to oncogenesis and cancer progression. In fact, these structural changes are important in understanding the implications of the adhesive properties of cancer cells [105, 106]. …”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
“…Several clinical trials of fucose-deficient mAbs are under way (22)(23)(24)(25)(26)(27), and mogamulizumab, an anti-CC chemokine receptor 4 mAb lacking core fucosylation has received marketing approval in Japan for the treatment of relapsed or refractory adult T-cell leukemia/ lymphoma (28). Other fucosylated glycans of interest include sialyl Lewis X (sLeX), sialyl Lewis A, and Lewis Y (LeY), which are on cell surfaces and have been associated with malignancy, tumor progression, and inflammation (6,21,29,30).…”
mentioning
confidence: 99%